The Impact of Electricity Price on Power-Generation Structure: Evidence From China - Wang, Jing; Li, Hong (Frontiers in Environmental Science, 2021)
Power-generation structure plays an essential role for a high-quality and sustainable development. It will be affected by a variety of factors. The focus of this paper is to evaluate the influence of electricity price. First, we provide a microeconomic framework to understand the impact mechanism. We discuss two effects through which price level can affect power generation, and then the power-generation structure. After that, an empirical test is conducted using provincial panel data, and the results of it are robust. We also test the above-mentioned mechanism empirically. There are two main conclusions. First, the electricity price has a positive effect on the share of thermal power in electricity generation. Second, mechanism test shows that, an increase of electricity price can not only improve efficiency of power plants, but also propel firms to invest in more renewable energy plants.